An Investigation into the Application of Maintenance Management Concept Based on Reliability Centered Maintenance of Tni-Al Fleet (Case Study of Corvette / Parchim Class) - D.K., Yanif; T.D., Iman (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2007)
The majority of TNI-AL war-ships, particularly of parchim class, are old and have been used for more than twenty years. It can be said, intuitively, that rate of degradation of diesel engine system lies in the wear-out period of a bathtub curve. The present paper is aimed to obtain and prove degradation pattern rate and level of risk from diesel engine system installed in KRI fleet of parchim class. Function of degradation rate of each diesel engine system is obtained from the most suitable distribution represent failure mode. Whilst, level of risk is determine with risk matrix. Weibull++ 4, a reliability software, was used to obtain parameters fit to each distribution.